A Complex Wavelet-Based OTFS Scheme for LEO Satellite Communication - Saifur Rahman Sabuj; Han-Shin Jo (IEEE Access)
This study investigates a wavelet-aided orthogonal time-frequency space (W-OTFS) modulation system operating in low earth orbit (LEO) satellite systems. The discrete wavelet transform (DWT) underlying the complex input signals (high-order modulation) is not applicable in the W-OTFS system because of increased performance errors and peak power. To overcome the problem of high-order modulation in W-OTFS systems, we propose combining the complex DWT paradigm with a newly developed W-OTFS modulation scheme, known as the complex W-OTFS (CW-OTFS) scheme. This paper presents a mathematical model for the proposed CW-OTFS system constructed using a straightforward matrix multiplication approach. The investigation utilized the complex form of the Haar and Daubechies wavelet functions. Additionally, the performance evaluation of the proposed scheme focused on analyzing the bit error rate (BER), peak-to-average power ratio (PAPR), and Cramér-Rao bound (CRB) characteristics for joint sensing and communications. The simulation findings demonstrate the superiority of the proposed CW-OTFS approach over existing state-of-the-art solutions in terms of the BER, PAPR, and CRB performance compared to the W-OTFS scheme in LEO satellite systems.